Factors Associated with Anemia Risk Behaviour in Teenage Girls: Literature Review - Nurhayati, Nurhayati; Lestari, Anisa Ayu; Rizki, Aprida Aulia (Pena Cendekia Insani, 2023)
Teenage girls are reluctant to take iron supplements, which makes it harder for the government to give them out. The coverage target is 25%, but North Sumatra only reached 19.96%, making it the fourth-lowest overall. The government hopes to reduce the number of such people by offering iron supplements to adolescent girls. The research conducted is a secondary research type of literature review. Literature Review is a series of activities related to the method of collecting literature, reading and recording and processing research materials . The method used is journal review. The articles used were research articles conducted in Indonesia regarding nutrition education for adolescents in an effort to prevent anaemia. The inclusion criteria for searching articles are: 1) Research articles published from 2018 to 2022, 2) Research articles in Indonesian language 3) Research articles can be downloaded in full text and free. Knowledge, attitude, education, and income are predisposing or risk factors contributing to adolescents' susceptibility to anemia. Factors such as information accessibility and infrastructure are examples of enabling factors. Parents, educators, and community leaders are factors that add weight or support to something